ANALISIS FAKTOR-FAKTOR PENERIMAAN DAN NIAT KEBERLANJUTAN PENGGUNAAN PORTAL AKADEMIK SIAKAD STMIK AKAKOM MENGGUNAKAN TAM SERTA MODEL DELONE DAN MCLEAN - Sur Yanti; Henry Nugroho (JURNAL INFORMATIKA DAN KOMPUTER, 2018)
Academic Portal SIAKAD STMIK AKAKOM with address siakad.akakom.ac.id, was built with the aim of improving the quality of performance and services as well as the means of academic interaction between lecturers, students and academic departments based on information technology. Evaluate the success of its application is necessary to always meet its objectives. Based on previous research and basic theory of TAM and DeLone and McLean model hence researcher make model to analyze acceptance factors and intention of sustainability use SIAKAD STMIK AKAKOM. Analyzer used is PLS 3.0. TAM describes the behavioral factors of computer users based on the beliefs, attitudes, intention, and user behaviour relationship. The DeLone and McLean model is an information system success model with three parts of the instrument, the first used to measure the technical success of the system quality, the two measures of semantic success ie the quality of information, and the three measures of effective information system is use, user satisfaction, individual impact and organizational impact. The results of empirical research indicate variable of Information Quality and System Quality that affect the User Satisfaction  towards SIAKAD STMIK AKAKOM, while the sustainability intention using SIAKAD STMIK AKAKOM determined by User Satisfaction variable.